1I/'Oumuamua as an N2 Ice Fragment of an Exo‐Pluto Surface II: Generation of N2 Ice Fragments and the Origin of 'Oumuamua. Issue 5 (13th May 2021) - Desch, S. J.; Jackson, A. P.
Abstract: The origin of the interstellar object 1I/'Oumuamua has defied explanation. In a companion paper (Jackson & Desch, 2021), we show that a body of N2 ice with axes 45 m × 44 m × 7.5 m at the time of observation would be consistent with its albedo, nongravitational acceleration, and lack of observed CO or CO2 or dust. Here we demonstrate that impacts on the surfaces of Pluto‐like Kuiper belt objects (KBOs) would have generated and ejected ∼10 14 collisional fragments—roughly half of them H2 O ice fragments and half of them N2 ice fragments—due to the dynamical instability that depleted the primordial Kuiper belt. We show consistency between these numbers and the frequency with which we would observe interstellar objects like 1I/'Oumuamua, and more comet‐like objects like 2I/Borisov, if other stellar systems eject such objects with efficiency like that of the Sun; we infer that differentiated KBOs and dynamical instabilities that eject impact‐generated fragments may be near‐universal among extrasolar systems. Galactic cosmic rays would erode such fragments over 4.5 Gyr, so that fragments are a small fraction (∼0.1%) of long‐period Oort comets, but C/2016 R2 may be an example. We estimate 'Oumuamua was ejected about 0.4–0.5 Gyr ago, from a young (∼10 8  yr) stellar system, which we speculate was in the Perseus arm. Objects like 'Oumuamua may directly probe the surface compositions of a hitherto‐unobserved type of exoplanet: "exo‐Plutos." 'Oumuamua may be the first sample of an exoplanet brought to us. Plain Language Summary: Our Kuiper belt originally had much more mass than today, but an instability caused by Neptune's migration disrupted their orbits, ejecting most of this material from the Solar System, and simultaneously causing numerous collisions among these bodies. There were thousands of bodies like Pluto, with N2 ice (like the gas in Earth's atmosphere, but frozen) on their surfaces, and this instability would have generated trillions of N2 ice fragments. A similar fragment, generated in another solar system, after traveling for about a half billion years through interstellar space, would match the size, shape, brightness, and dynamics of the interstellar object 1I/'Oumuamua. The odds of detecting such an object, as well as more comet‐like objects like the interstellar object 2I/Borisov, are consistent with the numbers of such objects we expect in interstellar space if most stellar systems ejected comets and N2 ice fragments with the same efficiency our solar system did. This implies other stellar systems also had Kuiper belts and similar instabilities. There are hints that some N2 ice fragments may have survived in the Oort cloud of comets in our Solar System. 'Oumuamua may be the first sample of an exoplanet born around another star, brought to Earth. Key Points: A dynamical instability in the early Kuiper belt likely ejected ∼10 15 N2 ice fragments from thousands of Plutos A fragment of N2 ice from an "exo‐Pluto" would match all known attributes of the interstellar object 1I/'Oumuamua The dynamical instability in the Kuiper belt experienced by our Solar System may be common among stellar systems